Measuring unsafe abortion-related mortality: a systematic review of the existing methods. - Caitlin Gerdts; Divya Vohra; Jennifer Ahern (PLoS ONE, 2013)
Background The WHO estimates that 13% of maternal mortality is due to unsafe abortion, but challenges with measurement and data quality persist. To our knowledge, no systematic assessment of the validity of studies reporting estimates of abortion-related mortality exists. Study design To be included in this study, articles had to meet the following criteria: (1) published between September 1(st), 2000-December 1(st), 2011; (2) utilized data from a country where abortion is "considered unsafe"; (3) specified and enumerated causes of maternal death including "abortion"; (4) enumerated ≥100 maternal deaths; (5) a quantitative research study; (6) published in a peer-reviewed journal. Results 7,438 articles were initially identified. Thirty-six studies were ultimately included. Overall, studies rated "Very Good" found the highest estimates of abortion related mortality (median 16%, range 1-27.4%). Studies rated "Very Poor" found the lowest overall proportion of abortion related deaths (median: 2%, range 1.3-9.4%). Conclusions Improvements in the quality of data collection would facilitate better understanding global abortion-related mortality. Until improved data exist, better reporting of study procedures and standardization of the definition of abortion and abortion-related mortality should be encouraged.